2014
DOI: 10.1074/jbc.m114.589085
|View full text |Cite
|
Sign up to set email alerts
|

The PsbP Domain Protein 1 Functions in the Assembly of Lumenal Domains in Photosystem I

Abstract: Background:The assembly of Photosystem I requires additional protein factors. Results: Arabidopsis RNAi mutants of PPD1 were characterized for Photosystem I function and assembly. Conclusion: The PPD1 protein serves as a factor to facilitate functional assembly of Photosystem I. Significance: RNAi suppression of PPD1 provides new details on its function in Photosystem I assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…First, PPD1, like PSA2, localizes to the thylakoid lumen (9). Second, the accumulation of PsaG is especially sensitive to the partial loss of PPD1 (10). Finally, PPD1 is found in a complex that comigrates with the PSA2-PsaG complex in native gels (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…First, PPD1, like PSA2, localizes to the thylakoid lumen (9). Second, the accumulation of PsaG is especially sensitive to the partial loss of PPD1 (10). Finally, PPD1 is found in a complex that comigrates with the PSA2-PsaG complex in native gels (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…This process necessitates the coordinated assembly of subunits and prosthetic groups at the thylakoid membrane where PSI is situated. Several factors have been described that are required for the assembly of PSI but that are not found in the mature complex; these include the chloroplast-encoded proteins Ycf3 and Ycf4 (4 -6) and the nucleus-encoded proteins Y3IP1 (7), Pyg7 (8), and PPD1 (9,10). Additional proteins mediate the association of prosthetic groups with PSI subunits (11)(12)(13)(14).…”
Section: Photosystem I (Psi)mentioning
confidence: 99%
“…The PSI biosynthesis pathway is still rather poorly characterized (Schöttler et al, 2011). Even if the PSI-LHCI assembly steps remain elusive, several auxiliary proteins have been identified that transiently assist the biogenesis and assembly of PSI (for review, see Schöttler et al, 2011), and novel PSI assembly factors are discovered constantly (Liu et al, 2012;Fristedt et al, 2014;Roose et al, 2014).…”
mentioning
confidence: 99%
“…9). By contrast, PSA2 and another luminal PSI assembly factor, PPD1, are found in smaller complexes of approximately 350 kD (Fristedt et al, 2014;Roose et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ycf3, Ycf4, and Y3IP1 associate with the stromal face of the thylakoid membrane, and they have been suggested to participate in the assembly of the stromal ridge (Boudreau et al, 1997;Ruf et al, 1997;Ozawa et al, 2009;Albus et al, 2010;Krech et al, 2012). PPD1 and PSA2 associate with the lumenal face of the thylakoid membrane (Liu et al, 2012;Fristedt et al, 2014;Roose et al, 2014), whereas PYG7 is an integral membrane protein (Stöckel et al, 2006). A recent study of the PYG7 ortholog in Chlamydomonas reported that it is required for PSI biogenesis specifically in the presence of molecular oxygen, which led to a model in which PYG7 shields Fe-S clusters or the cysteines that bind them from oxidation during PSI assembly (Heinnickel et al, 2016).…”
mentioning
confidence: 99%